Social justice in the economy as a conceptual framework of state regulatory policy - Петруненко, Ярослав Вікторович; Петруненко, Я. В.; Петруненко, Ярослав Викторович; Petrunenko, Yaroslav V.; Petrunenko, I. (Rushing Water Publishers Ltd., 2020)
Achieving social justice in the economic sphere is one of the priorities on the path to European integration, building a legal, democratic, and social state. An important role in this process is played by the substantive orientation of the state regulatory policy. With that, it should be emphasised that the concept of social justice in the economy, although not a new phenomenon, however, in its historical and legal development has acquired a new meaning, necessitating a reorientation of state regulatory policy to the modern meaning of this principle. Therefore, the scientific substantiation of ways to ensure the implementation of the principle of social justice in the economy in the process of state regulation of economic activity is an important area of research of modern legal science. Thus, the purpose of the study in this paper is to define the concept of social justice in the economy, indicators of its achievement, as well as to outline the prospects for the development of the concept of social justice in this area, including modern European doctrine. To achieve this purpose, the paper recourses to general theoretical, special and intersectoral methods of scientific knowledge, in particular, the epistemological method underlies the framework for formulating the definition of “social justice in the economy” and other concepts related to the subject, the analytical method allowed to identify indicators of achievement of social justice in the economy in the process of implementation of state regulatory policy, comparative legal method allowed to conduct a comparative analysis of ways and directions of achieving social justice in the European Community and Ukraine in state regulation of economic activity, methods of legal modelling and forecasting concepts of social justice in the economy.

Досягнення соціальної справедливості в економічній сфері є одним із пріоритетів на шляху до європейської інтеграції, побудови правової, демократичної та соціальної держави. Важливу роль у цьому процесі відіграє змістовна спрямованість державної регуляторної політики. При цьому слід підкреслити, що концепція соціальної справедливості в економіці, хоча і не є новим явищем, проте в своєму історико-правовому розвитку набула нового значення, що вимагає переорієнтації державної регуляторної політики на сучасний зміст цього принципу. Тому наукове обґрунтування шляхів забезпечення реалізації принципу соціальної справедливості в економіці в процесі державного регулювання економічної діяльності є важливим напрямом досліджень сучасної юридичної науки. Таким чином, метою дослідження в даній роботі є визначення поняття соціальної справедливості в економіці, показників її досягнення, а також окреслення перспектив розвитку концепції соціальної справедливості в цій галузі, включаючи сучасну європейську доктрину. Для досягнення цієї мети в роботі використано загальнотеоретичні, спеціальні та міжгалузеві методи наукового пізнання, зокрема, гносеологічний метод лежить в основі системи формулювання визначення поняття «соціальна справедливість в економіці» та інших пов’язаних понять, аналітичний метод дозволив виявити показники досягнення соціальної справедливості в економіці в процесі реалізації державної регуляторної політики, порівняльно-правовий метод дозволив провести порівняльний аналіз шляхів та напрямків досягнення соціальної справедливості в Європейському Співтоваристві та Україні в державному регулюванні економічної діяльності, методи правового моделювання та прогнозування концепцій соціальної справедливості в економіці.

Достижение социальной справедливости в экономической сфере является одним из приоритетов на пути к европейской интеграции, построения правового, демократического и социального государства. Важную роль в этом процессе играет содержательная направленность государственной регуляторной политики. При этом следует подчеркнуть, что концепция социальной справедливости в экономике, хотя и не является новым явлением, однако в своем историко-правовом развитии приобрела новое значение, требует переориентации государственной регуляторной политики в современный смысл этого принципа. Поэтому научное обоснование путей обеспечения реализации принципа социальной справедливости в экономике в процессе государственного регулирования экономической деятельности является важным направлением исследований современной юридической науки. Таким образом, целью исследования в данной работе является определение понятия социальной справедливости в экономике, показателей ее достижения, а также определение перспектив развития концепции социальной справедливости в этой области, включая современную европейскую доктрину. Для достижения этой цели в работе использованы общетеоретические, специальные и межотраслевые методы научного познания, в частности, гносеологический метод лежит в основе системы формулировка определения понятия «социальная справедливость в экономике» и других связанных понятий, аналитический метод позволил выявить показатели достижения социальной справедливости в экономике в процессе реализации государственной регуляторной политики, сравнительно-правовой метод позволил провести сравнительный анализ путей и направлений достижения социальной справедливости в Европейском Сообществе и Украине в государственном регулировании экономической деятельности, методы правового моделирования и прогнозирования концепций социальной справедливости в экономике.
Petrunenko I. Social justice in the economy as a conceptual framework of state regulatory policy / I. Petrunenko // Asia Life Sciences. – V. 22 (2). – Rushing Water Publishers Ltd., 2020. – P. 675-686.
Keywords: Community service; Economic activity; Legal society; Social justice; Socialist doctrine; State regulation; громадські служби; економічна діяльність; правове суспільство; соціальна справедливість; соціалістична доктрина; державне регулювання; общественные службы; экономическая деятельность; правовое общество; социальная справедливость; социалистическая доктрина; государственное регулирование; Research Subject Categories::LAW/JURISPRUDENCE